Rekonstruksi Hak dan Kewajiban Anggota Keluarga dalam Mewujudkan Keharmonisan Rumah Tangga: Telaah Normatif dalam Perspektif Hukum Islam - Hikmatullah, Hikmatullah; Wardana, Sendi (Tasyri' : Journal of Islamic Law, 2025)
A harmonious family is not just a dream, but a real goal that can be achieved through awareness, commitment, and joint efforts between family members. The household is not only a physical place to live, but also a space to build togetherness, trust, and love that are able to survive in the face of various life dynamics. This research aims to reconstruct the understanding of the rights and obligations of family members in realizing domestic harmony based on the perspective of Islamic law. The method used is normative legal research with a statute approach, which intensively studies legal literature, especially the Compilation of Islamic Law (KHI), as primary legal material, and is supported by secondary legal material. The results of the study show that household harmony (sakinah, mawaddah, and rahmah) is not solely determined by material aspects, but rather by the fulfillment of rights and obligations proportionally by each family member. True happiness is born from an attitude of mutual understanding, trust that is maintained, and commitment in carrying out each other's roles and responsibilities. This finding provides a conceptual contribution for married couples to rearrange the pattern of family relations that are just and sustainable in accordance with the principles of Islamic law.